2021
DOI: 10.1186/s12885-021-08005-1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of alectinib versus ceritinib in patients with advanced non–small-cell lung cancer of anaplastic lymphoma kinase fusion in whom crizotinib treatment failed

Abstract: Background Crizotinib is the approved treatment for advanced non-small cell lung cancers (NSCLCs) of anaplastic lymphoma kinase (ALK) fusion. Failure of crizotinib treatment frequently involves drug intolerance or resistance. Comparison of using second-generation ALK inhibitors in this setting remains lacking. Methods Sixty-five ALK-positive advanced NSCLC patients receiving second-generation ALK inhibitors following treatment failure of crizotinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Assessment of Alectinib vs Ceritinib in ALK-Positive NSCLC in Phase 2 Trials and Real-world Data estimates. However, given that comparisons of trial data vs RWD and RWD vs RWD produced consistent findings and that findings of a beneficial effect of alectinib from this study appear to be consistent with a retrospective analysis of progression-free survival and objective response in a cohort of patients in Taiwan for the same indication, 24 overall conclusions from this study are expected to be robust. Besides OS, there may be other patient-important measures of effectiveness (eg, toxicity) that were not examined in this study.…”
Section: Jama Network Open | Oncologysupporting
confidence: 76%
See 2 more Smart Citations
“…Assessment of Alectinib vs Ceritinib in ALK-Positive NSCLC in Phase 2 Trials and Real-world Data estimates. However, given that comparisons of trial data vs RWD and RWD vs RWD produced consistent findings and that findings of a beneficial effect of alectinib from this study appear to be consistent with a retrospective analysis of progression-free survival and objective response in a cohort of patients in Taiwan for the same indication, 24 overall conclusions from this study are expected to be robust. Besides OS, there may be other patient-important measures of effectiveness (eg, toxicity) that were not examined in this study.…”
Section: Jama Network Open | Oncologysupporting
confidence: 76%
“…Besides OS, there may be other patient-important measures of effectiveness (eg, toxicity) that were not examined in this study. However, prior retrospective analyses suggest that alectinib may be associated with fewer adverse events than ceritinib . Note that unbiased estimation of treatment effects using weighting depends on correct specification of the propensity model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 The high CNS protection activity of alectinib was also reported in a retrospective analysis in select patients with advanced ALK -positive NSCLC failing crizotinib treatment; patients receiving alectinib experienced a lower incidence of CNS progression than those receiving ceritinib (cause-specific HR 0.10, 95% CI 0.01-0.78). 15 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rebiopsy to discover the resistant mutations might be considered to determine the optimal treatment for ALK-inhibitor-resistant NSCLC [79]. In retrospective studies of ALK-positive advanced NSCLC, ceritinib demonstrated a longer median PFS compared to crizotinib for first-line treatment [80], and a second-generation ALK inhibitor, alectinib demonstrated a lower incidence of CNS progression and a tendency toward superior PFS compared to ceretinib in specific patients who had progressed on crizotinib [81].…”
Section: Alkmentioning
confidence: 99%